Fluid replacement needs of well-trained male and female athletes during indoor and outdoor steady state running - White, J. A.; Pomfret, D.; Rennie, S.; Gissane, C.; Wong, J.; Ford, M. (Journal of Science and Medicine in Sport, 1998)
Twelve male and six female well-trained middle distance athletes performed a series of six one hour runs at 75% VO2 peak pace under similar environmental states indoors (treadmill) and outdoors (track). Running was undertaken in control (C, no fluid), followed by water (W) and sports drink (SD) treatments, with each run separated by a one week interval. Both fluid treatments were supplied in volumes equivalent to individual body mass (fluid) losses incurred in the respective indoor and outdoor C treatments. Haemodynamic (plasma volume), physiological (heart rate and body temperature) and blood chemistry (blood lactate and glucose) measures were analysed as pre to post run changes (delta values). During the respective indoor and outdoor C treatments, males demonstrated approximately a twofold change in body mass (fluid) losses (delta 1.81 +/- 0.10 kg and 2.06 +/- 0.13 kg) compared with females (delta 0.93 +/- 0.11 kg and 1.32 +/- 0.12 kg) (all p<0.05). These losses resulted in almost a twofold fluid replacement need relative to body mass during the running phases of respective indoor and outdoor W and SD treatments in males compared with females (all p<0.05). Both W and SD treatments were effective in minimising the pre to post run disturbances in plasma volume, heart rate, body temperature and blood lactate, while SD treatment resulted in enhanced blood glucose changes. The results suggest gender specific differences in fluid replacement needs during steady state running, which need to be incorporated into fluid replacement strategies to compensate for the demands of training and competition in middle distance athletic events.